A study on the optimal selection of similar materials for the physical simulation experiment based on rock mineral components. (October 2022) - Hai-feng, Lu; Kai, Zhang; Jin-long, Yi; Ai-chao, Wei
Highlights: Physical model test is an important method to study engineering failure problems. Mineral components have a significant influence on the strength and deformation characteristics of rocks. A new method to prepare the similar materials was found according to the mineral component of rock. Abstract: The physical model test can effectively solve the problems of great difficulty and the high cost of the field test. Similarity theory is an essential basis for model test design. Accurate and rapid selection, proportioning, and production of similar materials are of great significance in accurately simulating the project site's rock stratum geological situation. However, the existing preparation methods of similar materials have great blindness and a low success rate. Considering the critical influence of mineral composition on the physical and mechanical properties of rock, aiming at preparing rock sample materials in TBM tunneling simulation under high ground stress, this paper takes Sichuan white sandstone as the specific research object. We use mineral composition to guide similar materials' mix design and preparation. It is found that similar materials with the required geometric similarity ratio can be obtained by adjusting the water-cement ratio and cement content under the condition that the mineral composition is basically the same. The similar material sample of Sichuan white sandstone with a given geometric similarity ratio (a(a＞1.5)) can be designed with cement content (C) as C = 150a -1 and water cement ratio (Wrt ) as Wrt = 0.072a + 0.108. We believe this method can also provide a reference for preparing similar materials for other rocks.